Analisis Internship Bagi Peningkatan Kompetensi Mahasiswa - Lutfia, Dinar Dinasty; Rahadi, Dedi Rianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
The most important aspect in undergoing an internship (internship) is to produce students who are more ready to undergo the world of work and professionally, which is carried out through internship activities. With internship activities, students can find out what skills they have so far. This study aims to determine the effect of internships on student competencies. This type of research uses qualitative research, namely, the data obtained is theory development and describes theory. The data collection technique was carried out using observation and interviews which were conducted through question and answer between the researcher and the resource person. The results of the case studies show that the internship program has a very meaningful role or contribution for students to improve the competence of soft skills & hard skills. And it also shows that the habits and attitudes that students have are very important compared to the knowledge and skills that can be obtained in a short time and increasing student competence through apprenticeship programs can reach professional standards and serve as a provision for experience for working in the next place. Keywords : Internship, competence, soft skill, hard skill